PERAN HUMAS DALAM MANAJEMEN PEMASARAN JASA PENDIDIKAN DI MA ALMU’AWANAH PAMULUTAN OGAN ILIR - Afif Alfiyanto; Febriyanti Febriyanti; Maryance Maryance; Muhammad Imanuddin; Fitri Hidayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the role of public relations in the marketing management of educator services at MA Almu'awwanah Pamulutan Ogan Ilir, as well as the supporting and inhibiting factors. The research method used is a qualitative method with a descriptive approach. Primary data sources consist of vice-principals in public relations, school principals, and public relations staff. Secondary data sources are documentation and observation data. Data collection techniques using observation, interviews, and documentation. The results of the study indicate that the role of public relations in the marketing management of educational services is, 1) participating in the implementation; 2) all parties communicate with each other and provide feedback; 3) evaluation is always carried out on each implementation of the marketing management of educational services through regular meetings. Factors that support the marketing management of educational services, namely 1) school achievement; 2) community interest; 3) supportive school leaders; and 4) strategic school location. Inhibiting factors, namely 1) lack of human resources; and 2) competition with other schools.